2018
DOI: 10.1111/cge.13140
|View full text |Cite
|
Sign up to set email alerts
|

TSGA10 is a novel candidate gene associated with acephalic spermatozoa

Abstract: Acephalic spermatozoa is a rare teratozoospermia associated with male infertility. However, the pathogenesis of this disorder remains unclear. Here, we report a 27 years old infertile male from a consanguineous family, who presented with 99% headless sperm in his ejaculate. Electron microscopic and immunofluorescence analysis suggested breakage at the midpiece of the patient's sperm cells. Subsequent whole-exome sequencing analysis identified a homozygous deletion within TSGA10 (c.211delG; p.A71Hfs*12), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 21 publications
3
75
0
3
Order By: Relevance
“…No significant differences were observed between semen parameters of the two patients harboring PMFBP1 mutations compared to those of patients with mutations in other genes ( SUN5 , TSGA10, and BRDT ) and in the PMFBP1 gene in the recent published work . However, sperm with round or amorphous heads were found in the ejaculate of our two patients, in addition to low sperm concentration (Table ).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…No significant differences were observed between semen parameters of the two patients harboring PMFBP1 mutations compared to those of patients with mutations in other genes ( SUN5 , TSGA10, and BRDT ) and in the PMFBP1 gene in the recent published work . However, sperm with round or amorphous heads were found in the ejaculate of our two patients, in addition to low sperm concentration (Table ).…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies found that SUN5 mutations cause breakage between the head and mid-piece of the tail, 6 while TSGA10 mutations lead to breaks within the mid-piece region. 11 Based on our findings in the present study using immunostaining with to connect the coupling apparatus and the caudal portion of the sperm head. 19 In the present study, we also examined the expression and localization of SUN5 and TSGA10 in the acephalic sperm from patients harboring PMFBP1 mutations.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations